Laparoscopic treatment of a simple hepatic cyst using argon beam coagulation - Yuki Ogasawara; Susumu Yamada; Kyoko Suzuki; Kaoru Obinata; Akane Hashizume; Shigeki Tomita; Tadaharu Okazaki (Elsevier, 2018)
Although simple hepatic cyst (SHC) is frequently detected incidentally during screening imaging examinations, consensus is lacking regarding the management of SHC, resulting in considerable confusion and difficulty in selecting therapy for children. We report a pediatric case of SHC treated laparoscopically using an argon beam coagulator. Keywords: Liver cyst, Laparoscopic deroofing, Argon beam coagulator, Child